Efficient integrated weed management practices for higher productivity and profitability in vegetable pea (Pisum sativum var. hortense) - SINGH, D P; RAJIV, RAJIV; KUMARI, MEENAKSHI; PRAKASH, H G (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was conducted on vegetable pea (Pisum sativum L. var. hortense) at Vegetable Research Station, Chandra Shekhar Azad University of Agriculture and Technology, Kanpur during 2014–17 to develop efficient integrated weed management practices. Seven different treatments, viz. pendimethalin @0.75 kg a.i./ha (pre-emergence), pendimethalin @0.75 kg a.i./ha (pre-emergence) + one hand weeding at 40 DAS, glyphosate @1.0 kg a.i./ha 15 days before sowing, glyphosate @1.0 kg a.i. /ha + one hand weeding at 40 DAS, mulching with black polythene, straw/grass mulch, hand weeding thrice at 20, 40 and 60 DAS were tested against two checks, i.e. weed free and weedy check (no weeding) in randomized block design with three replications. Vegetable pea variety ‘Azad Pea-3’ was used in the experiment. Crop was raised with recommended package of practices except treatments. Based on pooled data, among different treatments excluding weed free check, pendimethalin @0.75 kg a.i./ha (preemergence) + one hand weeding at 40 DAS recorded highest plant height (58.75 cm), seed weight/plant (12.73 g), number of seeds/pod (6.55), 100-seeds weight (31.93 g), seed yield (15.96 q/ha), seedling length (17.76 cm), seed vigour index–I (1619.92) and seed vigour index- II (13.17). In case of net return the same treatment also recorded significantly highest B:C ratio (2.30). Thus, pendimethalin @0.75 kg a.i./ha(pre-emergence) + one hand weeding at 40 DAS proved to be most profitable integrated weed management practice for vegetable pea.